Endurance : Shackleton's incredible voyage - Lansing, Alfred (New York, NY : Basic Books, 2007)
The astonishing saga of polar explorer Ernest Shackleton's survival for over a year on the ice-bound Antarctic seas, as Time magazine put it, "defined heroism." Alfred Lansing's scrupulously researched and brilliantly narrated book has long been acknowledged as the definitive account of the Endurance's fateful trip. This new edition has been augmented with maps and illustrations
"First published by Caroll & Graf in 1986"--T.p. verso
Keywords: Shackleton, Ernest Henry, -- Sir, -- 1874-1922 -- Travel -- Antarctica; Endurance (Ship); Antarctica -- Discovery and exploration